The book collectors : a band of Syrian rebels and the stories that carried them through a war - Minoui, Delphine (Farrar, Straus and Giroux, 2020)
"An extraordinary account of a band of young men in a besieged Damascan suburb who find books in the rubble and create a secret library"--